Global Sex and Labor Trafficking Participation Modes: Strategic Implications - Murray, Vernon; Solin, Julia; Shea, Holly (Journal of Leadership, Accountability and Ethics, 2021)
We analyzed participation modes for sex and labor trafficking victims from a large, global, sample. Results indicate that most victims are “Willing Assimilators.” Thus, they are “voluntarily” (i.e., no interpersonal coercion) trafficked (e.g., due to economic desperation), and cease working at will. The percentages of coerced victims are twice as high for sex trafficking compared with labor. Information regarding which strangers to trust when pursuing sex work or traditional work should reduce subsequent enslavement. Similarly, better information may help potential “Enlightened Apostates” (i.e., lured and enslaved by a loved one) decide which types of friends and relatives to trust.